Uniforest Connect - Digitalisation in Forestry Technology - Grobelnik, Sandi; Horvat, Robert (International Conference Fluid Power 2025: Conference Proceedings, 2025)
As with most modern equipment, both for leisure and industrial purposes, there is an increasing demand for monitoring machine operating parameters via mobile devices. This allows for easy insight into the condition of the machine, monitoring of work performance, alerts about potential problems, and preventive maintenance. The aim of the project is to provide users of forestry machines with a very easy insight into the heart of the machine. All important parameters and data that end users, owners of multiple machines – companies and dealers – want to monitor are recorded there. Therefore, it is necessary to enable wireless connection of forestry machines with smart devices (phones, tablets, etc.), through which users will be able to access the machine's data. This will provide users with much better information about the machine's condition. It also makes it easier to diagnose faults on the machines. This helps the manufacturer, the service technicians, and, on the other hand, the user to minimise unwanted machine downtime.